Магнитотеллурические функции отклика 3D модели глубинных разломов - Бурахович, Т.К.; Гищук, О.В.; Причепий, Т.И. (Геоінформатика, 2017)
На основе теоретического 3D моделирования природного низкочастотного электромагнитного поля получены магнитотеллурические функции отклика в рамках представления импеданса как в классическом виде — тензорном, так и в скалярном. Показано, что наклон субвертикального проводника наиболее ярко проявляется в соотношении уровня кривых рk и рζ (приподнятые и опущенные), направленных поперек структуры, относительно уровней локально-нормальной кривой и кривой вдоль проводника. В последней сложнее определить пространственное положение аномалии, его возможно обнаружить только по частотному сдвигу минимума и только непосредственно над проводником. Фазовые кривые импеданса, направленные поперек аномальной структуры, несут информацию об относительном изменении рk. На підставі теоретичного 3D моделювання природного низькочастотного провідника електромагнітного поля отримано магнітотелуричні функції відгуку в рамках зображення імпедансу як у класичному вигляді — тензорному, так і скалярному. Показано, що нахил субвертикального провідника найяскравіше проявляється у співвідношенні рівня кривих рk і рζ (підняті й опущені), спрямованих поперек провідної структури щодо рівня локально-нормальної кривої та рівня кривої вздовж провідника. В останній складніше визначити просторове положення аномалії, його можливо виявити тільки за частотним зсувом мінімуму і лише безпосередньо над провідником. Фазові криві імпедансу, що напрямлені поперек аномальної структури, несуть інформацію про відносну зміну рk. Purpose. The purpose of the paper is to calculate and analyze magnetovariation and a magnetotelluric response function of the 3D object type of high conductivity regional deep fault with different angles. The authors obtained the presentation of the impedance both as a classical-tensor, and a scalar one.
Design/methodology/approach. For calculations we used a software package of 3D modeling low-frequency electromagnetic fields, Mtd3fwd.
Findings. We have found that the deviation of the actual components of a comprehensive induction tipper of model M90 from M60 and M30 is 10% and 30%, respectively. It is concluded, with some degree of certainty, that it is possible to use leading deep faults in subvertical structures to build 3D models of real geological environments. Values pζ and рк (at polarization of telluric current across the top structure) stand for the relative value of the slope and the tilt direction of the modeled object, which were obtained from the scalar and tensor impedances. The values and behavior of curves Pζ are identical to curves рk, namely рху . Unlike рk, pζ was calculated according to only one field polarization.
Practical value/implications. The deep fault with different tilt angles M90-M30 is most evident in the ratio of curves рk (raised and lowered) directed transverse to the top structure, both relative to the level of a locally normal curve, and the level curve along the conductor. In the latter, it is difficult to determine the spatial position of anomalies, which may only be detected by the frequency shift minimum, and only directly above the conductor. The curves of phase impedance also signal relative changes in the apparent electrical resistance, with the curves directed transverse to the anomalous structure being most sensitive to it.